2021
DOI: 10.3390/biology10060558
|View full text |Cite
|
Sign up to set email alerts
|

High Fecal Contamination and High Levels of Antibiotic-Resistant Enterobacteriaceae in Water Consumed in the City of Maputo, Mozambique

Abstract: In the city of Maputo, Mozambique, food and water are often sold on the streets. Street water is packaged, distributed, and sold not paying attention to good hygienic practices, and its consumption is often associated with the occurrence of diarrheal diseases. Coincidentally, the increase of diarrheal diseases promotes the inappropriate use of antibiotics that might cause the emergence of antibiotic-resistant bacterial strains. In this context, the present study aimed to assess the microbiological quality of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Another important fact associated with the contamination of horticultural products, is the type of water used for irrigation, which sometimes comes from the sewage disposal. In addition, the absence of toilet or any type of hygiene facilities or even more the inadequate water for personal hygiene [ 69 ], in this area could contribute to the occurrence of the parasites in the fruits and vegetables produced [ 13 , 19 , 66 , 70 , 71 ]. Although we observed the lowest contamination rates in the products tested in the production zone, some pathogenic species ( G. duodenalis and nematodes) were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Another important fact associated with the contamination of horticultural products, is the type of water used for irrigation, which sometimes comes from the sewage disposal. In addition, the absence of toilet or any type of hygiene facilities or even more the inadequate water for personal hygiene [ 69 ], in this area could contribute to the occurrence of the parasites in the fruits and vegetables produced [ 13 , 19 , 66 , 70 , 71 ]. Although we observed the lowest contamination rates in the products tested in the production zone, some pathogenic species ( G. duodenalis and nematodes) were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Our surveillance has limited information on the conditions that the piped water were stored, or in what extent would be safe for consumption after storage. Most of the Mozambican pipelines are old and damaged in some sections aligned with the fact that are not properly maintained [39,40], which can contribute for contamination of the piped water mainly in flood situation as the supply network are emerged [39,41,42]. A recent study conducted in the capital of the country (Maputo), which analyzed different sources of water (home bottled, piped and supply well water) observed higher microbiological contamination than recommended for human consumption in piped water [42].…”
Section: Plos Onementioning
confidence: 99%
“…Most of the Mozambican pipelines are old and damaged in some sections aligned with the fact that are not properly maintained [39,40], which can contribute for contamination of the piped water mainly in flood situation as the supply network are emerged [39,41,42]. A recent study conducted in the capital of the country (Maputo), which analyzed different sources of water (home bottled, piped and supply well water) observed higher microbiological contamination than recommended for human consumption in piped water [42]. Although the study was carried out in Maputo, the company that supplies water at the national level is the same.…”
Section: Plos Onementioning
confidence: 99%
“…Of these, 31 food isolates were recovered from 83 street food samples and isolated according to the ISO 16649-2 [20], as described in Salamandane et al [1]. The other 28 E. coli isolates were recovered according to ISO 9308-1 [21], from a total of 118 water samples consumed in the city of Maputo, including home-bottled street water, tap water, and water from supply wells, as described previously [22]. The evaluation of the microbiological quality of the samples indicated that in general, the samples were unsatisfactory for consumption.…”
Section: Methodsmentioning
confidence: 99%
“…Biochemical tests were carried out to characterize these presumptive E. coli isolates from chromogenic medium, namely Gram staining, catalase, and oxidase tests [1,22]. Subsequently, molecular identification was performed, targeting the 16S rRNA gene (401 bp) with the AB035924 forward primer (5 CCC CCT GGA CGA AGA CTG A-3 ) and the AB035924 reverse primer (5 -ACC GCT GGC AAC AAA GGA T-3 ), as previously reported [1,22]. Subsequently, the 59 isolates were characterized by antibiotic resistance profiling, PFGE subtyping, and the detection of virulence genes and antibiotic resistance genes as described below.…”
Section: E Coli Isolatesmentioning
confidence: 99%